LEGAL PROTECTION FOR SKINCARE USERS THAT DOES NOT HAVE A PRODUCTION LICENSE REVIEW OF THE CONSUMER PROTECTION ACT - Siska Diana Sari; Arief Budiono; Dita Ajeng Yulianie (Universitas Muhammadiyah Mataram, 2020)
This article discusses consumer protection against skincare users. Skincare is a series of products that support skin health, improve appearance and maintain skin condition. Skin care products have different ingredients that skin needs. Skincare is a number of daily routine items carried out by a number of women, to achieve the desired results. It is this factor that attracts women to look for safe but effective skin care products in making white, eliminating dark spots, eliminating acne to blackheads in the female skin area. However, there are a number of individuals from skin care manufacturers making skin care with ingredients that are unsafe for skin health. Using empirical legal research method that is research that serves to look at the law in a clear sense and examine the role of law in society. Sociological law research, because it interacts with the community. This method is taken based on field facts. As for the results of this study, that a number of individuals from skin care manufacturers make products using ingredients that are not safe for the health of consumers' skin. Consumer protection is taken as any action and under the law, taken by the government with the aim of protecting consumers and obtaining legal certainty. To protect consumer rights, governments and consumers must play an active role, because businesses or manufacturers have many ways to trick consumers.Keywords: consumer protection; skin care products. Artikel ini membahas perlindungan konsumen terhadap pengguna skincare. Skincare adalah serangkaian produk yang mendukung kesehatan kulit, meningkatkan penampilan dan menjaga kondisi kulit. Produk perawatan kulit memiliki bahan berbeda yang dibutuhkan kulit. Skincare adalah sejumlah item rutin harian yang dilakukan oleh sejumlah wanita, untuk mencapai hasil yang diinginkan. Faktor inilah yang menarik wanita untuk mencari produk perawatan kulit yang aman namun efektif dalam membuat putih, menghilangkan bintik-bintik gelap, menghilangkan jerawat hingga komedo di area kulit wanita. Namun, ada sejumlah individu dari produsen perawatan kulit membuat perawatan kulit dengan bahan-bahan yang tidak aman untuk kesehatan kulit. Menggunakan metode penelitian hukum empiris yaitu penelitian yang berfungsi untuk memandang hukum dalam arti yang jelas dan meneliti peran hukum dalam masyarakat. Penelitian hukum sosiologis, karena pihaknya berinteraksi dengan masyarakat. Metode ini diambil berdasarkan fakta lapangan. Adapun hasil penelitian ini, bahwa sejumlah individu dari produsen perawatan kulit membuat produk menggunakan bahan-bahan yang tidak aman untuk kesehatan kulit konsumen. Perlindungan konsumen diambil sebagai tindakan apa pun dan berdasarkan undang-undang, yang diambil oleh pemerintah dengan tujuan melindungi konsumen dan mendapatkan kepastian hukum. Untuk melindungi hak konsumen, pemerintah dan konsumen harus berperan aktif, karena bisnis atau produsen memiliki banyak cara untuk mengelabui konsumen.